Prediction of octave noise spectra in accomodations in the superstructure of a ship - SZCZERBICKI, Edward; SZUWARZYŃSKI, Andrz (Archives of Acoustics, 1983)
This paper presents the results of the second stage of investigations aimed at the development of an effective method for predicting noise levels in accomodations in the superstructure of ships. The present procedure is based on a statistical model of multiple regression and uses standard results of noise measurements on board ships. It permits prediction of noise levels in 6 octave bands over the frequency range 63-2000 Hz, with an accuracy comparable to those of the equivalent foreign methods.